2021
DOI: 10.3390/v13122341
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Persistence of Putative Lytic and Temperate Bacteriophages in Vaginal Metagenomes from South African Adolescents

Abstract: The interaction between gut bacterial and viral microbiota is thought to be important in human health. While fluctuations in female genital tract (FGT) bacterial microbiota similarly determine sexual health, little is known about the presence, persistence, and function of vaginal bacteriophages. We conducted shotgun metagenome sequencing of cervicovaginal samples from South African adolescents collected longitudinally, who received no antibiotics. We annotated viral reads and circular bacteriophages, identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…We further examined FRT bacteriophage contigs to identify bacteriophage lifestyle and found the majority of identified contigs contained genes consistent with lysogeny. A recent study using metagenomic sequencing to examine the FRT microbiome in South African adolescents also found a high proportion of identified lysogenic phages in the FRT [26]. However, the larger sample size in our study allowed us to further evaluate for the difference by clinical BV diagnosis, revealing significantly more contigs containing lysogenic genes (including integrase, transposase, repressor, and recombinase genes) in BVpositive than BV-negative samples.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We further examined FRT bacteriophage contigs to identify bacteriophage lifestyle and found the majority of identified contigs contained genes consistent with lysogeny. A recent study using metagenomic sequencing to examine the FRT microbiome in South African adolescents also found a high proportion of identified lysogenic phages in the FRT [26]. However, the larger sample size in our study allowed us to further evaluate for the difference by clinical BV diagnosis, revealing significantly more contigs containing lysogenic genes (including integrase, transposase, repressor, and recombinase genes) in BVpositive than BV-negative samples.…”
Section: Discussionmentioning
confidence: 53%
“…Another group examining a cohort of BV-positive and BVnegative Danish women found no significant difference in viral (including bacteriophage) nor bacterial alpha diversity between BV-positive and BV-negative women [25]. A recent investigation of FRT bacteriophages in South African adolescents showed prevalence and persistence of prophages, but the sample size was small, with only 13 participants [26].…”
Section: Introductionmentioning
confidence: 96%
“…We leveraged previously generated lateral vaginal wall shotgun metagenome sequencing data (i.e., from DNA extracted from swabs without VLP-enrichment, described in Happel et al [ 27 ]) from participants of the same cohort to identify additional complete HPV genomes and report on these here. Briefly, the UW NWGC performed whole metagenome library preparation, quantitation and sequencing of genomic DNA using an Illumina NovaSeq 6000 S4 flow cell.…”
Section: Methodsmentioning
confidence: 99%
“…Phages also impact human health by infecting bacteria forming human microbiomes in the gut, respiratory tract, skin, or vagina. Happel et al [ 9 ] investigated the prevalence and persistence of (pro)phages and their associations with the vaginal bacterial community composition in the female genital tract of 13 South African adolescents, who received no antibiotics. The shotgun metagenome sequencing of cervicovaginal samples collected longitudinally showed that the most prevalent phage family was Siphoviridae , followed by Myoviridae , Podoviridae , Herelleviridae , and Inoviridae .…”
mentioning
confidence: 99%
“…The results pointed out that some prophages were present in cervicovaginal secretions of multiple participants, suggesting that prophages, and thus bacterial strains, are shared between adolescents. Shaping the biodiversity of bacterial populations, these viruses contribute to local fluctuations in the vaginal microbiome [ 9 ].…”
mentioning
confidence: 99%